Analysis of playing area dimensions in spanish professional soccer: extrapolation to the design of small-sided games with tactical applications - Caro, O.; Zubillaga, A.; Fradua, L.; Fernandez-Navarro, J. (The Journal of Strength and Conditioning Research, 2021)
The aims of this study were to examine (a) the width and length dimensions of the playing area in 4v4 situations during competition, (b) the influence of the pitch zone where the ball is on 4v4 dimensions, and (c) the influence of match status on the dimensions of 4v4 situations. Data were collected from 25 matches from the Spanish La Liga of the 2007-2008 season using the Amisco system. Length, width, and individual playing area (IPA) of the rectangle that included the nearest 4 players to the ball from each team were collected in a total of 8,727 4v4 game situations. The pitch zone and match status were also considered for these 4v4 situations. To determine factors that affect 4v4 game situations, 1-way analysis of variance was used. The influence of the pitch zone where 4v4 situations took place showed significant differences (p < 0.001) between the zones where different principles of the game apply. The areas of the 4v4 situations ranged from 14.70 ± 4.69 × 17.18 ± 6 to 17.09 ± 5.16 × 20.34 ± 5.93 m, and the IPA of the 4v4 playing rectangle ranged from 46.33 ± 20 to 35.48 ± 16.95 m2, being larger in the central zones of the pitch. The length of the 4v4 rectangle showed a significant reduction in the closer zones to the goal. Match status did not affect the dimensions of these 4v4 game situations significantly. The findings of this study suggest that the size of 4v4 situations proposed for training should be designed according to the pitch zone where playing actions take place.